2005
DOI: 10.1002/elps.200410276
|View full text |Cite
|
Sign up to set email alerts
|

The molecular end effect and its critical impact on the behavior of charged-uncharged polymer conjugates during free-solution electrophoresis

Abstract: Recently two novel techniques using free-solution electrophoresis to separate charged-uncharged polymer conjugates have proven successful: end-labeled free-solution electrophoresis (ELFSE) for DNA sequencing, and free-solution conjugate electrophoresis (FSCE) for molar mass profiling of uncharged polymers. The approach taken to analyze the experimental data was an extension of the theory of Long and co-workers (Long, D., Dobrynin, A. V., Rubinstein, M., Ajdari, A., J. Chem. Phys. 1998, 108, 1234-1244) for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…We have neglected the end effects predicted by Long et al [17], for which we amended our theory specifically for ELFSE in a previous paper [18]. These effects, confirmed experimentally in [19], result from monomers near the end of the ELFSE conjugate receiving a higher weighting in the average determining the mobility.…”
Section: Optimizing the Read Lengthmentioning
confidence: 83%
See 1 more Smart Citation
“…We have neglected the end effects predicted by Long et al [17], for which we amended our theory specifically for ELFSE in a previous paper [18]. These effects, confirmed experimentally in [19], result from monomers near the end of the ELFSE conjugate receiving a higher weighting in the average determining the mobility.…”
Section: Optimizing the Read Lengthmentioning
confidence: 83%
“…We note that the approach taken assumes that the linearization procedure of Long and coworkers, where the electric and hydrodynamic forces are considered independently and then superposed, is still a valid approximation for high field strengths (and/or large labels). We also note that, for simplicity, we are neglecting the end effects that were predicted by the theory of Long et al [17] and subsequently examined and confirmed for the case of ELFSE [18,19].…”
Section: Forces At Work In Segregated Conjugatesmentioning
confidence: 96%
“…(1) was recently re-examined theoretically [26]. Whereas previous theory assumed that each monomer unit (after rescaling the uncharged monomers by a 1 ) contributes equally to the electrophoretic mobility of the composite molecule, more recent theory has taken into account end-effects originally described by Long et al [27].…”
Section: Theory Of End-effects In Elfsementioning
confidence: 98%
“…The normalized weighting function c(n/N) of a Gaussian polymer chain was found in [26] to be well represented by the following function:…”
Section: Theory Of End-effects In Elfsementioning
confidence: 99%
“…Since the theory of ELFSE is rather well documented [9,10], we will use the classical model (described in Section 2) to analyze the recent experimental data (presented in Section 3) with linear and branched labels [8]. In order to compute the effective hydrodynamic radius of the various branched labels, we will first use the freely jointed chain (FJC) model and the equations derived by Teraoka [11] for branched FJC polymers.…”
Section: General Aspectsmentioning
confidence: 99%